Optimization of the operations and maintenance for wind farm using genetic algorithms - Rachid Mkhaitari; Yamina Mir; Mimoun Zazoui (Institute of Advanced Engineering and Science, 2023)
In Morocco, with the growing wind installed capacity it becomes crucial to perform further the O&M process, the wind assets are exposed to several constraints and raindom of maintenances for incidents. The target of this work is to optimize the gross and net production while simultaneously adhering to the minimum turbine unavailability and minimizing all contractual power curtailments due to unforeseeable factors. The proposed system is modeled using technical and mathematical formulas composed of the main function and the associated constraints. The project's modularization ends with a complex mathematical system that is non-linear, non-differentiable and requires the genetic algorithm for optimal resolution. Using Matlab to determine the optimized solution that represents the number of operational turbines per day, allowing for maximum production, minimizing curtailment, and reducing the unavailability of turbines. The 365-vector containing the numbers of turbines per day will opimally define the long-term O&M strategy.